Examining the behavioural intention to use hand sanitiser among Malaysian consumers during COVID-19 pandemic - Osman, Mohamed Syazwan; Che Ahmat, Nur Hidayah; Azmi, Azila; Ahmad, Zamri (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The COVID-19 pandemic has reshaped consumer behaviour in Malaysia, with a pronounced emphasis on health and safety. A substantial surge in the demand for hand sanitisers exemplifies this shift. Nevertheless, comprehensive studies investigating the behavioural intentions of Malaysian consumers concerning hand sanitiser use during the pandemic remain still need to be explored. This research addresses the gaps by studying Malaysian consumers' behavioural intentions concerning hand sanitiser utilisation during the pandemic. Guided by the theory of planned behaviour, we conducted a robust descriptive cross-sectional quantitative study. We developed the self-administered online survey and disseminated the survey link via diverse social media platforms, garnering 271 complete responses. Our analysis yields notable findings. Attitude, subjective norms, and perceived behavioural control emerge as influential factors, positively shaping the behavioural intentions of Malaysian consumers regarding hand sanitiser use during the pandemic. Notably, the attitude of Malaysian consumers stands out as a potent predictor of their behavioural intentions. These insights substantially contribute to consumer behaviour, specifically within the Malaysian pandemic context. Beyond their academic implications, our findings hold practical significance. Hand sanitiser producers can use the findings to effectively diversify their product offerings to meet heightened demand. Furthermore, the study's insights can assist the Malaysian government in gauging consumer adherence to standard operating procedures and their role in virus containment through hand sanitiser use. However, a geographical limitation exists, as a significant proportion of respondents’ hail from Malaysia's northern region, potentially limiting the generalizability of our results to the broader population. Overall, this study advances our understanding of consumer behaviour while offering actionable insights for industry stakeholders and policymakers. Study limitations and future research directions are also included.